0D/2D AgInS2/MXene Z-scheme heterojunction nanosheets for improved ammonia photosynthesis of N2. (July 2019) - Qin, Jiangzhou; Hu, Xia; Li, Xinyong; Yin, Zhifan; Liu, Baojun; Lam, Kwok-ho
Abstract: In order to explore efficient photocatalysts for N2 reduction reaction (NRR), 0D AgInS2 nanoparticles and 2D MXene (Ti3 C2 ) nanosheets with different mass ratios are employed for building Z-scheme heterostructures. The resultant hybrids exhibit excellent interfacial charge transfer ability according to their optical and photo-electro properties. As a result, the obtained composite (30 wt% AgInS2 ) shows significant improvement on the photocatalytic performance for N2 fixation with a high ammonia yield rate of 38.8 μmol/(g∙h) under visible-light illumination (>400 nm). Meanwhile, the DFT calculations show that the activation of N2 in a dinuclear end-on bound structure could lead to high adsorption energy (Ead  = −5.20 eV). Moreover, the mechanism of enhanced photocatalytic activity was proposed in terms of the quantum calculation between Ti3 C2 and N2 . This work provides new systems for enhanced NRR performance. Graphical abstract: Image 1 Highlights: The 0D/2D AgInS2 /MXene Z-scheme nanosheets were fabricated by in situ growth. The yield rate of N2 fixation could reach 38.8 μmol/(g∙h) under visible light. The mechanisms for enhanced activity were elucidated based on DFT and band alignment.